The Effect of Using Castor Oil on the Pollutants Emission in a Continuous Combustion Chamber - Hasan, Abdul Sattar J. M.; Hadi, Abdul Kadhim M. H.; Ekaab, Noora Saleh (Al-Nahrain Journal for Engineering Sciences, 2017)
This study investigates the effect of Castor oil on the pollutants emissions in the continuous combustion chamber. The bio-blend fuels used are mixtures of Castor oil with two types of hydrocarbon fuels (gas oil and kerosene). The pollutants measured include carbon monoxide CO, unburned hydrocarbon UHC, soot and nitrogen oxide NOx . It is found that all pollutants have less emissions when using Castor oil blended in different percentages of 5% , 7%, and 10% . The lower emission with Castor oil blends due to the existence of oxygen O2 in the chemical structure of the Castor oil which is sufficient to seek the complete combustion. The test were conducted through the range of equivalence ratio between (0.85-1.7) . Results showed that Castor oil blends with gas oil brings a reduction of about 71.2% in CO, 22.1% in UHC, 37.8% in NOx and 29.6% in soot emissions from that of pure gas oil. But, blends with kerosene, showed a reduction of about 70.6% in CO, 20% in UHC, 35.8% in NOx and 29% in soot emissions compared with those of pure kerosene.